High‐Throughput Optimization of Recombinant Protein Production in Microfluidic Gel Beads. Issue 2 (16th December 2020) - Napiorkowska, Marta; Pestalozzi, Luzius; Panke, Sven; Held, Martin; Schmitt, Steven
Abstract: Efficient production hosts are a key requirement for bringing biopharmaceutical and biotechnological innovations to the market. In this work, a truly universal high‐throughput platform for optimization of microbial protein production is described. Using droplet microfluidics, large genetic libraries of strains are encapsulated into biocompatible gel beads that are engineered to selectively retain any protein of interest. Bead‐retained products are then fluorescently labeled and strains with superior production titers are isolated using flow cytometry. The broad applicability of the platform is demonstrated by successfully culturing several industrially relevant bacterial and yeast strains and detecting peptides or proteins of interest that are secreted or released from the cell via autolysis. Lastly, the platform is applied to optimize cutinase secretion in Komagataella phaffii ( Pichia pastoris ) and a strain with 5.7‐fold improvement is isolated. The platform permits the analysis of >10 6 genotypes per day and is readily applicable to any protein that can be equipped with a His6 ‐tag. It is envisioned that the platform will be useful for large screening campaigns that aim to identify improved hosts for large‐scale production of biotechnologically relevant proteins, thereby accelerating the costly and time‐consuming process of strain engineering. Abstract : A high‐throughput platform for optimization of microbial protein production is presented. Strain libraries are encapsulated into microfluidic gel beads that selectively retain the protein of interest and allow for isolation of high producers by flow cytometry. The method is suitable for a wide range of secreted or intracellular proteins and is compatible with industrially relevant microbial production hosts.